Grizzly and polar bears as nonconsumptive cultural keystone species - Douglas Clark; Kyle Artelle; Chris Darimont; William Housty; Clyde Tallio; Douglas Neasloss; Aimee Schmidt; Andrew Wiget; Nancy Turner (Canadian Science Publishing, 2021)
Grizzly bears and polar bears often serve as ecological "flagship species" in conservation efforts, but although consumptively used in some areas and cultures they can also be important cultural keystone species even where not hunted. We extend the application of established criteria for defining cultural keystone species to also encompass species with which cultures have a primarily nonconsumptive relationship but that are nonetheless disproportionately important to well-being and identity. Grizzly bears in coastal British Columbia are closely linked to many Indigenous Peoples (including the Haíɫzaqv (Heiltsuk), Kitasoo/Xai'xais, and Nuxalk First Nations), where they are central to the identity, culture, and livelihoods of individuals, families, Chiefs, and Nations. Polar bears in Churchill, Manitoba, provide another example as a cultural keystone species for a mixed Indigenous and non-Indigenous community in which many of the livelihood benefits from the species are mediated by economic transactions in a globalized tourism market. We discuss context specificity and questions of equity in sharing of benefits from cultural keystone species. Our expanded definition of cultural keystone species gives broader recognition of the beyond-ecological importance of these species to Indigenous Peoples, which highlights the societal and ecological importance of Indigenous sovereignty and could facilitate the increased cross-cultural understanding critical to reconciliation.